(untitled) (International Journal of Engineering and Computer Science, 2016)
Now a days, a wide variety of security system requires reliable recognizable scheme to either confirm or identify the person from a group. Due to the characteristics of EEG, it is very difficult to forge or copy the EEG signal. In this paper, for feature extraction-multiwavelet transforms are used. For classification, kNN method is used.